ENHANCING STUDENTâS ACHIEVEMENT IN THE SIXTH THEME OF THE BEAUTY OF MY COUNTRY THROUGH SCIENTIFIC APPROACH OF PROBLEM BASED LEARNING MODEL IN THE CLASS IV - Sulistiyowati, Nurngaeni; Harmianto, Sri; Pamujo, Pamujo (Dinamika, 2015)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  The research aimed to enhance studentsâ achievement in the sixth theme of the beauty of my country and the first sub theme about the variety of animal and plants through scientific approach of problem based learning model. The subjects were the students of class VIB SD Negeri 2 Gombong Kebumen regency that consisted of 30 students, 19 female and 11 male ones. It was classroom action research that conducted in two cycles. There were three meeting for each cycle. Then each cycle consisted of planning, doing action, observing, and reflecting. The data was collected by using test and non test. The test was in the form of questions that used to measure the studentsâ achievement on the cognitive aspect. It was conducted in the end of every meeting in each cycle. The non test was in the form of observation and documentation. The result of the research showed that the learning process using scientific approach of problem based learning model is able to improve studentsâ achievement. In cycle I, in the cognitive skill, the mean score was 72,44 with the passing grade of 67,77%. In cycle II, the mean score was improved to 80with the passing grade of85,53%. The studentsâ achievement on the affective skill was 74,4% in cycle I and improved to 84,54% in cycle II. Then the studentsâ achievement on the phsycomotoric skill was 74% in cycle I and improved to 83,11%. Based on the result, it can be summed up that the thematic learning using scientific approach through problem based learning is able to improve the studentsâ achievement in class IVB SD Negeri 2 Gombong.Â Key words: Studentsâ Achievement, Animal and Plants, Scientific Approach,Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Problem Based LearningÂ